Tratamento de efluente de indústria de reciclagem de plástico por processo físico-químico em escala de bancada com coagulantes orgânicos e inorgânicos - Straioto, Henrique (2019)
This research aimed to perform the treatment of an effluent from the plastic washing processes of a recycling industry, located in the northern region of Paraná. At the bench scale, three coagulants were performed in physical chemical processes of coagulation, flocculation and sedimentation. The inorganic coagulant were polyaluminium chloride (PAC) and ferric chloride and the organic coagulant was tannin. The removal of turbidity, apparent color and chemical oxygen demand (COD) was study. The influences of three types of synthetic polymers (anionic, cationic and nonionic) was verify with the PAC coagulant. The determination of the number of tests and the optimal working points were made by the statistical method of central rotational composite design, with the results being read by the Statistica software, version 13.5.0. After determining the optimum points, further tests were performed at these points, aiming to find out the treatment efficiency in relation to the removal of total nitrogen, total phosphorus, total and suspended solids and changes in electrical conductivity and alkalinity. Coagulant and polymer dosages and coagulation pH were defined as variables. The research was conducted in the region of Londrina - PR, in the laboratories of the Federal Technological University of Paraná (UTFPR). The importance of research is mainly related to environmental issues, since with effluent treatment and a possible reuse of treated water, the capture of clean water and the discharge of polluted effluents in natural beds are reduced. By analyzing the contour graphs generated by the adopted statistical model, it was possible to verify that the highest turbidity, apparent color and COD removals were achieved by using the organic coagulant with dosages of approximately 80 mg.L-1 , or by applying dosages. of coagulant PAC between 25 and 35 mg.L-1 combined with dosages of flocculant polymers between 3 and 4 mg.L-1 . The maximum removal percentages were 99.97% for turbidity, 99.87% for apparent color and 99.59% for COD, which correspond to 0.10 NTU, 1 uH and 10.49 mg.L-1 turbidity, apparent color and residual COD.